2020
DOI: 10.1016/j.scitotenv.2020.140000
|View full text |Cite
|
Sign up to set email alerts
|

Significant changes in the chemical compositions and sources of PM2.5 in Wuhan since the city lockdown as COVID-19

Abstract: Differences in PM 2.5 chemical species and sources since lockdown were reported. • Primary emission reduced while secondary formation enhanced since lockdown. • Emission reduction dominated the improvement of air quality in Wuhan during lockdown.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

15
153
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
5
3
2

Relationship

1
9

Authors

Journals

citations
Cited by 204 publications
(169 citation statements)
references
References 75 publications
15
153
1
Order By: Relevance
“…Such a difference illustrated the great changes in the chemical components in PM 2.5 during the lockdown. Zheng et al (2020) reported that primary emission reduced while secondary formation enhanced since lockdown in Wuhan, the lockdown measures not only reduced the mass concentrations of air pollutants and associated chemical compositions, but also modified the diurnal variation patterns of PM 2.5 sources. Although traffic emissions are believed to have been greatly reduced during the lockdown, the NO 3 − /SO 4 2− ratio was found to be the lowest during the SF, probably due to the occurrence of the lowest proportion of NO 3 − (31.9%), ascribed to the decreased traffic emissions, and the highest SO 4 2− fraction (36.1%), caused by fireworks.…”
Section: Resultsmentioning
confidence: 99%
“…Such a difference illustrated the great changes in the chemical components in PM 2.5 during the lockdown. Zheng et al (2020) reported that primary emission reduced while secondary formation enhanced since lockdown in Wuhan, the lockdown measures not only reduced the mass concentrations of air pollutants and associated chemical compositions, but also modified the diurnal variation patterns of PM 2.5 sources. Although traffic emissions are believed to have been greatly reduced during the lockdown, the NO 3 − /SO 4 2− ratio was found to be the lowest during the SF, probably due to the occurrence of the lowest proportion of NO 3 − (31.9%), ascribed to the decreased traffic emissions, and the highest SO 4 2− fraction (36.1%), caused by fireworks.…”
Section: Resultsmentioning
confidence: 99%
“…At the same time, analyses of the changes in atmospheric composition over the last few months, and in the months to come with easing (and possible retightening) of COVID-19-based restrictions, will provide new insight into the detailed chemistry linking emissions and secondary air pollution 4,25,26 . Such analyses will also inform what policy interventions might be most efficient for improving future air quality.…”
Section: Opportunities For Improved Atmospheric Chemical Understandingmentioning
confidence: 99%
“…As a result, researchers began investigating the impact of these measures on air quality under the assumption that fewer people would be driving and thus there would be lower levels of traffic-related air pollutants (Abdullah et al, 2020;Dantas et al, 2020;Zambrano-Monserrate et al, 2020). Research groups in major cities such as Sao Paulo, Brazil; Wuhan, China; and Barcelona, Spain reported decreases in traffic-related air pollutant concentrations from January to May 2020 (Abdullah et al, 2020;Cadotte, 2020;Kambalagere, 2020;Li et al, 2020;Tobías et al, 2020;Zambrano-Monserrate et al, 2020;Zheng et al, 2020), which they suggest is a result of reduced vehicle emissions. Several studies have also shown similar reductions in pollutant concentrations by comparing 2020 concentrations to those measured in previous years (Chen et al, 2020;Dantas et al, 2020;Dutheil et al, 2020;Freitas et al, 2020;Isaifan, 2020;Muhammad et al, 2020;Nakada and Urban, 2020;Sharma et al, 2020;Xu et al, 2020).…”
Section: Introductionmentioning
confidence: 99%